At Your Doorstep: Online Food and Grocery Delivery Application - Kamaludin, Hazalila; Han, Loh Qiao; Abd. Ishak, Suhaimi; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2020)
This Online Food and Grocery Delivery Application is developed to solve the problem of individuals that do not have their own vehicle or lack of time to buy their own food and grocery. It is an application that will help individuals to buy halal food and grocery in Parit Raja, Batu Pahat. The application has been developed based on prototyping-based methodology which is used to produce a two-phase prototype and finally developed into a complete application. Software technology that used to develop this application is Ionic Framework. This application will help individuals to buy food and grocery without having to step outside of the house. In overall, it can be an alternative for the individuals that are facing some difficulty to purchase halal foods and groceries on their own.